2021
DOI: 10.3344/kjp.2021.34.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive effects of oleuropein in experimental models of neuropathic pain in male rats

Abstract: Background: The present investigation explored the therapeutic actions of oleuropein along with the possible signaling pathway involved in attenuating neuropathic pain in chronic constriction injury (CCI) and vincristine-induced neuropathic pain in male rats. Methods: Four loose ligatures were placed around the sciatic nerve to induce CCI, and vincristine (50 μg/kg) was injected for 10 days to develop neuropathic pain. The development of cold allodynia, mechanical allodynia, and mechanical hyperalgesia was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Mitragyna speciosa [181,182], Momordica charantia [183], and Nigella Sativa [184,185] (Table 4). Acmella oleracea Asteraceae Leaves and flowers [187] Acorus calamus Araceae Rhizomes [188] Alstonia scholaris Apocyanaceae Milky juice of plant [189] Butea monosperma Fabaceae Leaves [190] Crocus sativus Iridaceae Flower [191] Curcuma longa Zingiberaceae Roots [192] Emblica officinalis Phyllanthaceae Fruit [193] Euphorbia tirucalli Euphor-biaceae Latex, root, bark [194] Gelsemium elegans Loganiaceae Seeds, stems [195,196] Ginkgo biloba Ginkgoaceae Herbal extract [197,198] Momordica charantia Cucurbitaceae Fruit [199] Nauclea latifolia Rubiaceae Roots [200,201] Ocimum sanctum Lamiaceae Leaves [202] Olea europaea Oleaceae Oil and leaves [203] Paederia scandens Rubiaceae Roots, leaves, bark, and fruits [204] Punica granatum Punicaceae The juice, whole fruit, flowers, and roots [205] Senna spectabilis Fabaceae Flowers, fruits and leaves [206] Thymus caramanicus Jalas Lamiaceae Aerial parts [207] Tribulus terristris Zygophylla-Ceae Complete herb [208] Trigonella foenum-graecum Fabaceae Seeds [209] Vernonia cinerea Asteraceae Whole plant [210] Future prospective of N-type VGCC blockers…”
Section: Mechanism For Excitatory Effect Of Drugsmentioning
confidence: 99%
“…Mitragyna speciosa [181,182], Momordica charantia [183], and Nigella Sativa [184,185] (Table 4). Acmella oleracea Asteraceae Leaves and flowers [187] Acorus calamus Araceae Rhizomes [188] Alstonia scholaris Apocyanaceae Milky juice of plant [189] Butea monosperma Fabaceae Leaves [190] Crocus sativus Iridaceae Flower [191] Curcuma longa Zingiberaceae Roots [192] Emblica officinalis Phyllanthaceae Fruit [193] Euphorbia tirucalli Euphor-biaceae Latex, root, bark [194] Gelsemium elegans Loganiaceae Seeds, stems [195,196] Ginkgo biloba Ginkgoaceae Herbal extract [197,198] Momordica charantia Cucurbitaceae Fruit [199] Nauclea latifolia Rubiaceae Roots [200,201] Ocimum sanctum Lamiaceae Leaves [202] Olea europaea Oleaceae Oil and leaves [203] Paederia scandens Rubiaceae Roots, leaves, bark, and fruits [204] Punica granatum Punicaceae The juice, whole fruit, flowers, and roots [205] Senna spectabilis Fabaceae Flowers, fruits and leaves [206] Thymus caramanicus Jalas Lamiaceae Aerial parts [207] Tribulus terristris Zygophylla-Ceae Complete herb [208] Trigonella foenum-graecum Fabaceae Seeds [209] Vernonia cinerea Asteraceae Whole plant [210] Future prospective of N-type VGCC blockers…”
Section: Mechanism For Excitatory Effect Of Drugsmentioning
confidence: 99%
“…Alkaloid levo-corydalmine [ 94 ], antioxidant alphalipoic acid [ 95 ], mitoquinone [ 96 ], endogenous fatty acid amide palmitoylethanolamide (PEA) in association with oxazoline forming the 2-pentadecyl-2-oxazoline of palmitoylethanolamide (PEA-OXA) [ 97 ], curcumin [ 98 ], quercetin [ 99 ], resveratrol [ 100 ], formononetin [ 101 ], berberine [ 102 ], dimethyl fumarate and its metabolite monomethyl fumarate [ 103 ], and oleuropein [ 104 ] can reduce pain and inflammation associated with CIPN by activating the Nrf2 pathway. In addition to these Nrf2 inducers, Zhang and Xu shed light on the effects of bromodomain-containing protein 4 (BRD4) on the alleviation of vincristine-induced PN [ 105 ].…”
Section: Nrf2 Signaling and Its Inducers In Different Peripheral Neur...mentioning
confidence: 99%
“…In addition to the active constituents of garlic oil, several other natural compounds, including bromelain [ 113 ], a major protease from pineapple ( Ananas comosus ) [ 114 ], oleuropein, [ 104 ], paeoniflorin [ 115 ], a bioactive compound isolated from the dried roots of Paeonia lactifora Pallas or P. veitchii Lynch [ 115 ], the extracts from Thymus algeriensis and T. fontanesii ( Lamiaceae ) [ 116 ], quercetin [ 117 ], plumbagin [ 118 ], poly (ADP-ribose) polymerase (PARP) inhibitor 4-amino 1, 8-naphthalimide (4-ANI) [ 117 ], DOR agonist UFP-512 [ 119 ], and RTA-408 (a novel synthetic triterpenoid under clinical investigation) [ 120 ] ameliorated CCI-induced neuropathic pain. Targeted mechanisms reported involved either increasing the Nrf2 activity [ 104 , 114 , 116 , 117 , 119 , 120 ], enhancing the translocation of Nrf2 while suppressing the spinal NOD-like receptor protein 3 (NLRP3) inflammasome and NF-κB [ 115 ], or inhibiting PARP activation [ 117 ]. For example, Arruri et al reported that carvacrol attenuated CCI-induced neuropathic pain by inhibiting NLRP3 and activating autophagy via the Keap1/Nrf-2/p62 forward-feedback loop and augmenting mitochondrial quality control (MCQ) [ 121 , 122 ].…”
Section: Nrf2 Signaling and Its Inducers In Different Peripheral Neur...mentioning
confidence: 99%